Chromosomal abnormalities and copy number variations in fetal left‐sided congenital heart defects. (3rd February 2016) - Jansen, Fenna A. R.; Hoffer, Mariette J. V.; van Velzen, Christine L.; Plati, Stephani Klingeman; Rijlaarsdam, Marry E. B.; Clur, Sally‐Ann B.; Blom, Nico A.; Pajkrt, Eva; Bhola, Shama L.; Knegt, Alida C.; de Boer, Marion A.; Haak, Monique C.
Abstract: Objectives: To demonstrate the spectrum of copy number variants (CNVs) in fetuses with isolated left‐sided congenital heart defects (CHDs), and analyse genetic content. Methods: Between 2003 and 2012, 200 fetuses were identified with left‐sided CHD. Exclusion criteria were chromosomal rearrangements, 22q11.2 microdeletion and/or extra‐cardiac malformations ( n  = 64). We included cases with additional minor anomalies ( n  = 39), such as single umbilical artery. In 54 of 136 eligible cases, stored material was available for array analysis. CNVs were categorized as either (likely) benign, (likely) pathogenic or of unknown significance. Results: In 18 of the 54 isolated left‐sided CHDs we found 28 rare CNVs (prevalence 33%, average 1.6 CNV per person, size 10.6 kb–2.2 Mb). Our interpretation yielded clinically significant CNVs in two of 54 cases (4%) and variants of unknown significance in three other cases (6%). Conclusions: In left‐sided CHDs that appear isolated, with normal chromosome analysis and 22q11.2 FISH analysis, array analysis detects clinically significant CNVs. When counselling parents of a fetus with a left‐sided CHD it must be taken into consideration that aside from the cardiac characteristics, the presence of extra‐cardiac malformations and chromosomal abnormalities influence the treatment plan and prognosis. © 2015 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Left‐sided congenital heart defects (CHDs) can be part of malformation syndromes and/or display chromosomal abnormalities. Rare copy number variants (CNVs) contribute to CHDs. What Does This Study Add? Array analysis contributes to the diagnostic work up and can identify pathological CNVs in 4% of cases where the fetal karyotype/rapid aneuploidy detection and 22q11 FISH analysis are normal. Isolated left‐sided CHDs display large chromosomal abnormalities/22q11 microdeletion in 8%.